PENGABDIAN KEPADA MASYARAKAT PELATIHAN PEMBUATAN PETA DAERAH PENANGKAPAN RAJUNGAN (Portunus pelagicus) UNTUK MENINGKATKAN HASIL TANGKAPAN - Ihsan, Ihsan; Sulaiman, Muhammad (JURNAL PENGABDIAN MASYARAKAT KAUNIAH, 2022)
The use of small crab in the waters of Pangkep Regency has not been maximized, as one of the things done is mapping the ideal fishing area. This study aims to map the fishing area to increase the crab catches. The purpose of this research is to increase the efficiency and effectiveness of fishermen and to increase the income and standard of living of fishermen. The study was conducted in the waters of Pangkep Regency. Materials and tools used in this study include the global position system, current meter, hand repractometer, DO meter, and pH meter. The data used include primary data and secondary data. Primary data is collected through direct measurements in the field and secondary data obtained from documents that have been produced by related agencies. Data analysis was obtained from laboratory analysis and measurement and geographic information systems. The results of the research conducted were obtained. The location of the adult swimming catch area includes coastal waters, around the island and in particular the outer boundaries of the islands. The criteria for catching area of ​​the crab that is "in accordance" with the area of ​​the waters is 89,131.37 ha, "quite suitable" with the area of ​​the waters is 109,164.87 ha. The criteria for the area of ​​catching crabs that are "not suitable" with an area of ​​water is 4,577.56 ha.